Analisis kerapuhan struktur gedung Dinas Pertanian Kabupaten Pacitan dengan static adaptive pushover - Arum Narwastu; Senot Sangadji; Rida Handiana Devi; Hendramawat Aski Safarizki (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
Information from BMKG indicates an increase in earthquake occurences in Pacitan Regency in recent years, a phenomenon that has been noticeable to the local community. Considering that the building of the Pacitan District Agriculture Office has been standing for about five years, a structural performance analysis is needed to ensure the building's strength in resisting earthquake damage. This research aims to investigate the structural response of a building when subjected to structural analysis due to deformation caused by dynamic seismic forces using the Seismostruct software. In this study, an adaptive pushover method was developed, considering the stiffness and modal characteristics of the structure at different levels of inelasticity to update the distribution of lateral loads. This method also considers the location-specific spectrum for load scaling. The results showed that this new approach yielded static analysis results that closely approximated inelastic dynamic analysis and could predict the structural response in detail. The existing building structure will be modeled as a structure, including column and beam frames with material specifications and dead and live loads, based on data obtained following SNI 1726:2012 regulations. The structural behavior analysis will be conducted using the static adaptive pushover method. From this research, the maximum value of the capacity curve for the building under study occurred at a base shear of 2070.595 kN and a displacement of 0.060971 m. The converted spectral displacement was found to be 0.47 m with a slight limit state of 100%, a moderate limit state of 100%, an extensive limit state of 99%, and a complete limit state of 71%.